2012
DOI: 10.1002/chp.21118
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Management Plans of Doctors and Medical Students: An Illness Script Perspective

Abstract: The experienced physicians' accurate management plans are characterized by a high number of the Mx and Dx items. For sixth-year students the management plans are still incomplete, which leads to generic as well as inaccurate Mx orders. For fourth-year students, the Mx focus is lacking, and hence they seem to treat an Mx task as if it were a Dx task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The insignificant difference in correct key features score, common key feature score, and discriminative key features score in posttest compared to pretest may demonstrate that medical students tend to choose key features rather than being accurate. These findings are in line with previous studies that indicated medical students are relatively insensitive to the nature and circumstances of the task (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 92%
“…The insignificant difference in correct key features score, common key feature score, and discriminative key features score in posttest compared to pretest may demonstrate that medical students tend to choose key features rather than being accurate. These findings are in line with previous studies that indicated medical students are relatively insensitive to the nature and circumstances of the task (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 92%
“…The notion that illness scripts also contain treatment knowledge is also consistent with the nature of scripts as a variant of schemas, goal‐directed knowledge structures that emerge from real‐life events to help us perform tasks efficiently. Research on the role of scripts in treatment judgements is close to non‐existent, but studies have suggested that components of the illness scripts influence management decisions and that scripts indeed contain treatment knowledge . Apparently doctors activate diagnostic as well as treatment knowledge simultaneously when faced with a patient problem.…”
Section: The Cognitive Processes Underlying Doctors’ Decision Makingmentioning
confidence: 99%
“…The difference in pattern recognition between students and the expert groups might be a consequence of degree of prior experience with patients who have had similar problems. The matured pattern recognition develops accurate diagnosis and treatment strategy (26).…”
Section: Discussionmentioning
confidence: 99%